Urbanization, Informal Economy, and Spatial Inequality in Indonesian Cities: A Secondary Data-Based Analysis - Andi Ima Kesuma (International Journal of Technology and Education Research, 2026)
Urbanization in Indonesia has become a major driver of spatial transformation, economic restructuring, and social change. While urban growth creates opportunities for productivity, employment, and service concentration, it also intensifies spatial inequality, informal employment, housing pressure, and environmental vulnerability. This study revises the discussion of urbanization and city growth by using a secondary data-based qualitative analysis supported by recent demographic, urban, and development sources. Data were drawn from Statistics Indonesia, the World Bank, the United Nations Department of Economic and Social Affairs, UN-Habitat, and selected academic literature on urbanization, agglomeration, rural-urban migration, and the informal economy. The analysis shows that Indonesian urbanization should be understood not merely as rural-to-urban migration, but as a structural transformation shaped by uneven regional development, metropolitan concentration, labor-market segmentation, and land consumption dynamics. The informal sector functions as both a livelihood absorber and a symptom of incomplete urban economic transformation. The study argues that a more inclusive urban policy requires stronger rural development, integrated metropolitan governance, formal-informal sector linkage, affordable housing provision, and spatial planning that protects ecological buffer zones.